2021
DOI: 10.3390/ijms222413573
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Impairs Adipose Tissue Expansion and Cardiometabolic Profile in Obese-Diabetic Female Rats

Abstract: It has been reported that 17β-estradiol (E2) can exert beneficial effects against the development of obesity, providing women with a healthier metabolic profile and conferring cardiovascular protection. However, a growing body of evidence questions this role in the context of obesity and diabetes. We focus on the adipose tissue–heart axis to address the question of whether E2 can have metabolically detrimental effects in an obese-diabetic rat model. Female Zucker Diabetic Fatty rats were used: LEAN, fa/+; SHAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…To clarify this point further research is needed. Moreover, it is important to mention that in this study only male mice were studied, given that estrogens modify adipose tissue expansion as well as metabolic profile ( Martínez-Cignoni et al, 2021 ; Moreira-Pais et al, 2020 ). Furthermore, previous studies suggested that female mice would be protected against HFD-induced metabolic changes while maintaining an anti-inflammatory environment in the intra-abdominal adipose tissue ( Pettersson et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…To clarify this point further research is needed. Moreover, it is important to mention that in this study only male mice were studied, given that estrogens modify adipose tissue expansion as well as metabolic profile ( Martínez-Cignoni et al, 2021 ; Moreira-Pais et al, 2020 ). Furthermore, previous studies suggested that female mice would be protected against HFD-induced metabolic changes while maintaining an anti-inflammatory environment in the intra-abdominal adipose tissue ( Pettersson et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports contradict the results of this study. For instance, Martinez-Cignoni et al ( 36 ) showed that induction of ovariectomy in diabetic animals was associated with decreased CD36 expression. The reason for these contradictory results can be due to the difference in the type of injury and duration of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, oestrogens also influence the capacity of the adipocyte to be filled with lipid. As will be discussed further below, oestrogens also influence the nature of fat cells themselves, making them more ‘expandable’—which refers to the ability of the fat cell to store more calories [9,16,24]. Once a cell has reached its capacity to store lipid, lipid is deposited ectopically which is associated with increased inflammation and the metabolic syndrome.…”
Section: The Evolutionary Biology In Sex Differences Of Adipose Tissu...mentioning
confidence: 99%
“…The nutritional and metabolic demands for reproduction are significantly higher in women when compared to men. SAT deposition in females provides fuel during peak times of energy requirements such as during breastfeeding, which may account for the asymmetry seen in adipose tissue deposition [24].…”
Section: The Evolutionary Biology In Sex Differences Of Adipose Tissu...mentioning
confidence: 99%